HARUN AR-RASYID - Kasmiati, Kasmiati (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Harun ar-Rasyid was the third caliph of Abbasid. He served as a very predominant caliph in his time. Moreover, it was in his rule that, in Asia, there were many achievements in various sectors of life such as in economy, agriculture, science, and literature. Besides, buildings for worship, education, and health were founded at that time. The progress in these sectors of life made Baghdad, the capital of Abbasid, as the greatest center for commerce. The decline and destruction of Harun ar-Rasyidâs caliphate was preceded by caliph succession and the promotion of Ibrahim ibn Aqlab to be a governor as well as Rafiâah al-Laishâs rebellion to the dynasty in the epoch of Al-Maâmun.Â Â